Synthesis A Number of Amino Substitutions on Hexachlorocyclotriphosphazene - Al-Samarrai, Safaa A.; Al-Berag, Naba' N. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
(DPA)) 5Cl3N3(NAM)) and compound (2) (P5Cl3N3The preparation of compound (1) ((P ) of the reaction hexachlorocyclotriphosphazene (A) and 2(Bc)4Cl3N3and compound (3) ((P Nicotinamide (B), di phenylamine (C) and Benzocaine (D) at different rates and by the frared inIR -presence of triethylamine. The synthe sized compounds were characterized by FT P NMR spectrum. 31H,1 and spectrum